2012
DOI: 10.1186/1471-2458-12-1036
|View full text |Cite
|
Sign up to set email alerts
|

Family affluence and cultural capital as indicators of social inequalities in adolescent’s eating behaviours: a population-based survey

Abstract: BackgroundDietary inequality, via socio-economic inequality, may involve several mechanisms. Different aspects of adolescents’ socio-economic circumstances should therefore be considered in order to make effective interventions to promote healthy eating in the young population. Indicators designed to tap socio-economic status among adolescents in particular will facilitate a better understanding of the concept of socio-economic status and how it influences health behaviour among young people. The purpose of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
59
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 59 publications
8
59
0
7
Order By: Relevance
“…Of note, adolescents in countries with higher socioeconomic differences (e.g., developing countries) are reported to have worse health conditions [38], an earlier onset of smoking [1] and alcohol and drug abuse, more risky sexual behavior [38], and inappropriate eating behaviors [6]. …”
Section: Discussionmentioning
confidence: 99%
“…Of note, adolescents in countries with higher socioeconomic differences (e.g., developing countries) are reported to have worse health conditions [38], an earlier onset of smoking [1] and alcohol and drug abuse, more risky sexual behavior [38], and inappropriate eating behaviors [6]. …”
Section: Discussionmentioning
confidence: 99%
“…These inequalities interact with lifestyle factors, including dietary habits11 12 and physical activity,12 13 affecting body weight and obesity status 14. Furthermore, food insecurity, as a result of SES inequalities influences children's health and growth, while it is directly associated with obesity and inadequate nutrition quality 15 16.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that SES plays one of the key roles in the development of healthy eating habits in children [1,17], which tend to be carried into adulthood [18,19,20]. Significant associations have been documented between parental SES and the consumption of breakfast [7,9,21,22], a morning snack [9], dinner [21], fruit and vegetables [7,21,23,24,25] and dairy products (low and full-fat milk/yoghurt, chocolate milk, low and full-fat cheese and feta cheese) [7,25] in children and adolescents. Sweet beverages, processed and energy-dense foods have been inversely associated with family SES [1,6].…”
Section: Introductionmentioning
confidence: 99%